Analysing a disaster management field exercise with SOL‐methodology. (21st November 2018) - Jackovics, Peter; Czaban, Csaba
Abstract : Safety through Organisational Learning methodology, as a proven tool for supporting organisational learning from safety relevant events, means that an organisation conducts systematic analyses of accidents, incidents or near misses and feeds the resulting experience back to its members using an appropriate reporting or management system. It was the first time that SOL‐methodology was used for Evaluating an International Disaster Management Field Exercise by European Project Partners. The general purpose of the project was testing SOL as a post‐evaluating procedure for this full‐scale field exercise. It was an important declared goal to provide the European Union with a comprehensive picture about the process of the field exercise. The particular purposes of the event analysis were to identify the main individual, group or organisational reasons for, and key technological factors of, the events that occurred. Analysing with SOL allows the identification of concrete alternative corrective actions/measures by which the probability that similar events occur in the future can radically be reduced. Furthermore, such measures help organisational learning, thereby contributing to the development and maintenance of a long‐term, safe organisational culture.